Innovative approaches to the formation of an intellectual system of support of decision making during the solution of tasks of management of land resources. Issue 1 (October 2020) - Galchenko, S A; Antropov, D V; Komarov, S I; Zhdanova, R V; Kirillov, R A
Abstract: The article discusses innovative approaches to the formation of an intelligent decision support system for solving problems of land management, land use, cadastral and market valuation of lands, management of specially protected natural territories and objects. The research results can be used in the formation of intelligent management systems for the subsequent creation of an information resource digital platform for land use, the development of an information resource digital platform for intelligent management of agriculture and land use systems at the level of an economic entity and a region for the transition to a highly productive agricultural sector of a new technological structure, as well as for the adoption of effective managerial decisions, which will also increase the rationality and the possibility of involving land uses, subject to special protection, including those included in the territory of historical settlements and related to the territories of small towns. From the point of view of assessing agricultural land plots, or territories of cultural and historical interest, a complex of language and software tools designed to create, maintain and share a database by one or many users is one of the most promising methods of storage, processing and using data.